The (1)H NMR Spectroscopic Effect of Steric Compression Is Found in [3.3.1]Oxa- and Azabicycles and Their Analogues - Zeng, Ziyu (ACS Omega, 2021)
[Image: see text] The through-space (1)H NMR effect of steric compression by the lone-pair electrons of O- and N-atoms is shown in synthetic [3.3.1]oxa- and azabicycles. The electrons of the compressed proton bond are pushed away by the repulsive force generated by the lone-pair electrons of the heteroatom. There is a corresponding significant increase in the chemical shift of the compressed proton. The intensity of this deshielding effect is related to the proximity and overlap of the lone-pair or compressing atom. The steric compression decreases when the lone-pair electrons of the heteroatom and the compressed proton are not directly overlapped, for example, in [4.3.1]- and [3.2.1]azabicycles. Steric compression is also caused by a proton, deuterium, or an ethyl group close in space to the compressed proton. The protonated [3.3.1]azabicycle adopts a true-boat/true-chair conformation in its crystal lattice, but in solution the conformation is true-chair/true-chair.